Nutrient variations in boreal and subarctic Swedish rivers : Landscape control of land–sea fluxes - Humborg, Christoph; Smedberg, Erik; Blomqvist, Sven; Mörth, Carl-Magnus; Brink, Jenni; Rahm, Lars; Danielsson, Åsa; Sahlberg, Jörgen (Tema vatten i natur och samhälle, 2004)
We examined the hypothesis that the extent of vegetation cover governs the fluxes of nutrients from boreal and subarctic river catchments to the sea. Fluxes of total organic carbon (TOC) and dissolved inorganic nitrogen, phosphorus, and dissolved silicate (DIN, DIP, and DSi, respectively) are described from 19 river catchments and subcatchments (ranging in size from 34 to 40,000 km2) in northern Sweden with a detailed analysis of the rivers Lulea¨lven and Kalixa¨lven. Fluxes of TOC, DIP, and DSi increase by an order of magnitude with increasing proportion of forest and wetland area, whereas DIN did not follow this pattern but remained constantly low. Principal component analysis on landscape variables showed the importance of almost all land cover and soil type variables associated with vegetation, periglacial environment, soil and bedrock with slow weathering rates, boundary of upper tree line, and percentage of lake area. A cluster analysis of the principal components showed that the river systems could be separated into mountainous headwaters and forest and wetland catchments. This clustering was also valid in relation to river chemistry (TOC, DIP, and DSi) and was confirmed with a redundancy analysis, including river chemistry and principal components as environmental variables. The first axis explains 89% of the variance in river chemistry and almost 100% of the variance in the relation between river chemistry and landscape variables. These results suggest that vegetation change during interglacial periods is likely to have had a major effect on inputs of TOC, DIP, and DSi into the past ocean. Original publication: Christoph Humborg, Erik Smedberg, Sven Blomqvist, Carl-Magnus Mörth, Jenni Brink, Lars Rahm, Åsa Danielsson and Jörgen Sahlberg, Nutrient variations in boreal and subarctic Swedish rivers: Landscape control of land–sea fluxes, 2004, Limnology & Oceanology, (49), 5, 1871-1883. Copyright: American Society of Limnology and Oceanology, http://www.aslo.org/lo/